NMDA antagonist agents for the treatment of symptoms in autism spectrum disorder: a systematic review and meta-analysis - Dessus-Gilbert, Marie-Lou; Nourredine, Mikail; Zimmer, Luc; Rolland, Benjamin; Geoffray, Marie-Maude; Auffret, Marine; Jurek, Lucie (Frontiers in Pharmacology, 2024)
Aims: This systematic review and meta-analysis aimed to assess the efficacy of NMDA antagonists in ASD (Autism Spectrum Disorder) on the core (communication and social interaction, repetitive behavior) and associated symptoms (irritability) of ASD, as well as their safety. Methods: PubMed, CENTRAL, CINHAL, EMBASE, and PsycINFO databases were searched until November 2023. Two authors independently selected the studies and extracted data. Randomized controlled trials assessing the efficacy of NMDA receptor antagonists in participants with ASD aged < 18 years were included. The quality of the studies was assessed using the Risk of Bias-2 tool. A random-effect meta-analysis model was used to calculate standardized mean differences (SMD) or odds ratios (OR) using meta package in R. Results: This systematic review included ten studies (588 participants). Most studies did not report scales assessing core symptoms of ASD. Meta-analysis of efficacy on ASD core symptoms included three studies (248 participants). NMDA antagonists were not superior to placebo (SMD=0.29; CI95% [-1,94; 1.35]); I² = 0%). NMDA antagonists was not superior to placebo concerning response (four studies, 189 participants) (OR =2.4; CI95% [0.69; 8.38]); I2 = 35%). Meta-analysis of efficacy on irritability included three studies (186 participants); NMDA antagonists were not superior to placebo (MD irritability =-1.94; CI95% [-4.66;0.77]); I2 = 0%). Compared with placebo, significantly more participants in the NMDA antagonist group reported at least one adverse event (five studies, 310 participants) (OR=2.04; CI95% [1.17; 3.57]); I2 = 0%). Conclusions: Current evidence does not support the effectiveness of NMDA antagonists in the treatment of ASD symptoms or irritability. Further research is needed due to the limited and low quality data available. PROSPERO CRD42018110399